The strategic alignment: literature review (Business Vision, 2021)
The purpose of this article was to develop a review of the state of the art of the organizational variable strategic alignment, which has demonstrated its importance in achieving the effectiveness of corporate objectives, through its positive association with organizational resources such as: technologies information, leadership, organizational culture, human talent, dynamic capabilities, etc. In this way, we proceeded with the method of systematic review of the literature in three stages: planning of the review, execution of the review and preparation of the results report, through which procedure and through the use of the comparative technique, they selected relevant studies from journals and high impact scientific articles, especially from the Web Of Science database, in addition, the technique of evaluating Journals in databases such as SJR Scimago was used. The results determined that strategic alignment has its roots in the business field through the theory of contingency, which has been the subject of multiple studies, especially in the field of information technology and business management, and with little theoretical development in areas such as education, the tourism sector, the public sphere, medicine, psychology and other sciences. In addition, the need to deepen studies of strategic alignment in different organizational contexts has been revealed.
Keywords: Strategic Alignment; Strategic Coalignment; Information Systems Alignment